sFlt-1 Impairs Neurite Growth and Neuronal Differentiation in SH-SY5Y Cells and Human Neurons - Barron, Aaron (Portland Press, 2026)
Pre-eclampsia (PE) is a hypertensive disorder of pregnancy which is associated with increased risk of neurodevelopmental disorders in exposed offspring. The pathophysiological mechanisms mediating this relationship are currently unknown, and one potential candidate is the anti-angiogenic factor soluble Fms-like tyrosine kinase 1 (sFlt-1), which is highly elevated in PE. While sFlt-1 can impair angiogenesis via inhibition of VEGFA signalling, it is unclear whether it can directly affect neuronal development independently of its effects on the vasculature. To test this hypothesis, the current study differentiated the human neural progenitor cell (NPC) line ReNcell® VM into a mixed culture of mature neurons and glia, and exposed them to sFlt-1 during development. Outcomes measured were neurite growth, cytotoxicity, mRNA expression of nestin, MBP, GFAP, and βIII-tubulin, and neurosphere differentiation. sFlt-1 induced a significant reduction in neurite growth and this effect was timing- and dose-dependent up to 100 ng/mL, with no effect on cytotoxicity. sFlt-1 (100 ng/mL) also reduced βIII-tubulin mRNA and neuronal differentiation of neurospheres. Undifferentiated NPCs and mature neurons/glia expressed VEGFA and VEGFR-2, required for endogenous autocrine and paracrine VEGFA signalling, while sFlt-1 treatment prevented the neurogenic effects of exogenous VEGFA. Overall, these data provide the first experimental evidence for a direct effect of sFlt-1 on neurite growth and neuronal differentiation in human neurons through inhibition of VEGFA signalling, clarifying our understanding of the potential role of sFlt-1 as a mechanism by which PE can affect neuronal development.